HIV awareness, pre-exposure prophylaxis perceptions and experiences among people who exchange sex: qualitative and community based participatory study - Yasaswi Kislovskiy; Sarah Erpenbeck; Jamie Martina; Courtney Judkins; Elizabeth Miller; Judy C. Chang (BMC, 2022)
Abstract Background People who exchange sex for money, favors, goods or services, combat higher risk of acquiring sexually transmitted diseases (STDs) and human immunodeficiency virus (HIV). Understanding barriers to STD and HIV related healthcare from the perspective of this stigmatized and marginalized community may improve access to sexual health services including pre-exposure prophylaxis (PrEP).  Methods We used community-partnered participatory and qualitative methods to conduct anonymous one-on-one interviews with people who exchange sex to understand their perspectives and experiences related to pre-exposure prophylaxis (PrEP) to prevent HIV acquisition. We conducted twenty-two interviews and coded them to perform thematic analysis.  Results We identified five themes: (1) Appreciation of HIV risk and prevention strategies grew from information accumulated over time. (2) PrEP information came from a variety of sources with mixed messages and uncertain credibility. (3) Decision-making about use of PrEP was relative to other behavioral decisions regarding exchange sex. (4) The multi-step process of obtaining PrEP presented multiple potential barriers. (5) Healthcare providers were seen as powerful facilitators to PrEP utilization. Conclusions Our findings suggest that PrEP education and care needs to be made more relevant and accessible to individuals who exchange sex.